MEMAHAMI ARAH BARU SUPERVISI PENDIDIKAN SEBAGAI TINDAKAN MORAL - Muhamad Abdul Manan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
Education is important of issue for every aspect progress, human development and especially for our big nation. The context school is as education organization that needs supervision and assessment.The main role of superior is as coordinator, consultant, leader of club, and evaluator. Work of coordinator is as program which managed by staff member for studying and teaching. Work of consultant is giving help and consulate of problems experienced by teacher as individual or collective. Work of leader club is lead of teachers for developing cub potency when they develop of curriculum, subject and teacher professional needs. Executor is leader of supervision, supervisor and supervisor. They are responsible supervisor for existence and dynamics school as institution then hoped can be awaken nation potential in future. Superiors working considered for involve moral dynamics. Superiors moral activity have relationship by environment; as teachers relation and most urgent are relation to students and moral intrinsic of learning supervisor. No realize, sometimes supervision process did by supervisor which have moral element; basic moral of dimension must visible clear and assertive applied.